2013
DOI: 10.1371/journal.pone.0057182
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Acid Production by Streptococcus mutans with a Surface-Displayed pH-Sensitive Green Fluorescent Protein

Abstract: Acidogenicity and aciduricity are the main virulence factors of the cavity-causing bacterium Streptococcus mutans. Monitoring at the individual cell level the temporal and spatial distribution of acid produced by this important oral pathogen is central for our understanding of these key virulence factors especially when S. mutans resides in multi-species microbial communities. In this study, we explored the application of pH-sensitive green fluorescent proteins (pHluorins) to investigate these important featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 55 publications
2
44
0
1
Order By: Relevance
“…Recently, we reported the presence of compartmentalized acidic pH microenvironments in the interior of EPS-enmeshed microcolonies13. Using a surface-displayed pH sensitive fluorescent protein (pHluorins), Guo et al 45 also detected low pH values confined near the cell clusters linking our previous findings with acid accumulation within microcolonies. Here, we demonstrated that S. mutans EPS-matrix facilitates the generation of an acidic core within a 3D microcolony structure despite external exposure to a neutralizing buffer, which in turn activates bacterial gene expression in situ, mediating the biofilm microenvironment and bacterial activity locally.…”
Section: Discussionsupporting
confidence: 75%
“…Recently, we reported the presence of compartmentalized acidic pH microenvironments in the interior of EPS-enmeshed microcolonies13. Using a surface-displayed pH sensitive fluorescent protein (pHluorins), Guo et al 45 also detected low pH values confined near the cell clusters linking our previous findings with acid accumulation within microcolonies. Here, we demonstrated that S. mutans EPS-matrix facilitates the generation of an acidic core within a 3D microcolony structure despite external exposure to a neutralizing buffer, which in turn activates bacterial gene expression in situ, mediating the biofilm microenvironment and bacterial activity locally.…”
Section: Discussionsupporting
confidence: 75%
“…The results of our previous studies have shown that the synthesis of Gtf-derived glucans leads to the formation of an insoluble EPS-rich matrix scaffold that acts as a diffusion-limiting barrier (15). In parallel, the metabolic activity of S. mutans clustered within the microcolony can produce copious amounts of acids that accumulate locally (15,74). It is conceivable that the alterations in the extracellular matrix containing a dense population of bacterial cells help to prevent acid within the biofilm from diffusing outward, thus prolonging and intensifying the acid attack.…”
Section: Discussionmentioning
confidence: 99%
“…Our data reveal that defective assembly of EPS matrix and microcolony formation as a result of L-arginine exposure may also contribute to elevated in situ pH at the biofilm-sHA interface. Previous studies have shown that EPS-enmeshed microcolonies could trap acid at the sHA surface and/or restrict the access of neutralizing buffer to generate acidic microenvironments locally due to metabolic activity of the densely packed bacteria enmeshed within a diffusionlimiting EPS matrix, particularly at the deeper layers of the biofilm (6,57,58). Altogether, it appears that the combination of ADS activity and favorable ecological changes with disruption of EPS/ microcolony development may offer a more comprehensive explanation for the biofilm pH-related effects associated with L-arginine exposure.…”
Section: Discussionmentioning
confidence: 99%